Spinoza Now - Vardoulakis, Dimitris (Book collections on Project MUSE., 2011)
What does it mean to think about, and with, Spinoza today? This collection, the first broadly interdisciplinary volume dealing with Spinozan thought, asserts the importance of Spinoza's philosophy of immanence for contemporary cultural and philosophical debates. Engaging with Spinoza's insistence on the centrality of the passions as the site of the creative and productive forces shaping society, this collection critiques the impulse to transcendence and regimes of mastery, exposing universal values as illusory. "Spinoza Now" pursues Spinoza's challenge to abandon the temptation to th.